Scenedesmus obliquus mediated brewery wastewater remediation and CO2 biofixation for green energy purposes. (1st November 2017) - Ferreira, Alice; Ribeiro, Belina; Marques, Paula A.S.S.; Ferreira, Ana F.; Dias, Ana Paula; Pinheiro, Helena M.; Reis, Alberto; Gouveia, Luisa
Abstract: Microalgae can be used for wastewater bioremediation with simultaneous CO2 biofixation producing valuable biomass. Wastewater from a brewery was treated using the Scenedesmus obliquus microalga in bubble-column photobioreactors (PBRs). The PBRs were fed with ambient air and the effect of a 10% (v/v) brewery CO2 supplement was studied. The PBRs were inoculated and a range of mean hydraulic residence time (HRT) values were tested (2.1–10.4 days). The maximum ash-free dry weight (AFDW) biomass productivity was obtained for a HRT of 3.5 days (0.29 d −1 dilution rate; 0.2 g L −1 d −1 (in terms of AFDW). The highest pollutant removal efficiencies were 92.9 and 88.5% for ammonia and total nitrogen, respectively, 40.8% for phosphorus, and 61.9% for COD. Except a dilution rate of 0.48 d −1 trial, the treated wastewater always met the Portuguese legislation quality standard for discharge into natural water bodies. Aiming to simultaneously maximize biomass volumetric productivity, CO2 biofixation rate and wastewater treatment efficiency, while minimizing residence time, 0.29 d −1 represents the optimal dilution rate value. The potential of the produced Scenedesmus obliquus biomass was evaluated for the generation of biohydrogen through dark fermentation with Enterobacter aerogenes, and of bio-oil, bio-char and bio-gas through a pyrolysis process. The yields obtained were 67.1 mL H2 g −1 (in terms of volatile solids - VS) for bioH2 and 64, 30 and 6% for bio-oil, bio-char and bio-gas, respectively (dry mass content (%) calculated over freeze dryer biomass basis). Highlights: Scenedesmus obliquus treats successfully brewery effluents (liquid and gaseous). An HRT of 3.5 days assured the highest biomass productivity and efficient treatment. The biomass produced was valued by bio and thermochemical conversion to bioenergy. S. obliquus produces 167.8 mL H2  L −1 FM by dark fermentation, in mesophilic regime. The yields were: 64, 30 and 6% for bio-oil, bio-char and bio-gas, respectively.